Relationship between job satisfaction, work environment, and employee performance: a case study of a Bangladesh's logistic company - Hosen, Md Delowar (2022)
The purpose of this research is to determine the relationship between job satisfaction, work environment, and employee engagement towards employee performance among the logistics industries in Bangladesh. Job satisfaction, work environment, and employee engagement are the independent factors, whereas employee performance is the dependent variable. A total of 155 employees took part in this study by filling out a survey form. Data was gathered using 48-item questionnaires with a five-point Likert scale and 6 demographic questions. Descriptive statistics (mean and standard deviation) and inferential statistics were used to analyze the data (correlation and multiple regressions). The results of this research show that, job satisfaction and employee engagement have a substantial association with employee performance, however work environment has no significant relationship with employee performance. Meanwhile, the parameters investigated explain 39.1 percent of employee performance, according to the multiple regression results. Job satisfaction is the most influential component, followed by employee engagement, while the work environment has the least or no influence. This research showed researcher to figure out issues of employees in this department balance job satisfaction, work environment, employee engagement, and employee performance.